Enduring identities : the guise of Shinto in contemporary Japan - Nelson, John K. (John Kenneth), 1953- (Honolulu : University of Hawai'i Press, 2000)
Annotation Enduring Identities is an attempt to understand Shinto's continuing relevance to the cultural identity of contemporary Japanese. The enduring significance of this ancient yet innovative religion is evidenced each year by the millions of Japanese who visit its shrines. They might come merely seeking a park-like setting or to make a request of the shrine's deities, asking for a marriage partner, a baby, or success at school or work; or they might come to give thanks for benefits received through the intercession of deities or to legitimate and sacralize civic and political activities. Through an investigation of one of Japan's most important and venerated Shinto shrines, Kamo Wake Ikazuchi Jinja (more commonly Kamigamo Jinja), the book addresses what appears through Western and some Asian eyes to be an exotic and incongruous blend of superstition and reason as well as a photogenic juxtaposition of present and past. Combining theoretical sophistication with extensive field-work and a deep knowledge of Japan, John Nelson documents and interprets the ancient Kyoto shrine's yearly cycle of rituals and festivals, its sanctified landscapes, and the people who make it viable. At local and regional levels, Kamigamo Shrine's ritual traditions (such as the famous Hollyhock Festival) and the strategies for their perpetuation and implementation provide points of departure for issues that anthropologists, historians, and scholars of religion will recognize as central to their disciplines. These include the formation of social memory, the role of individual agency within institutional politics, religious practice and performance, the shaping of sacred space and place, ethnic versus culturalidentity, and the politics of historical representation and cultural nationalism. Nelson links these themes through a detailed ethnography about a significant place and institution, which, until now, has been largely closed to both Japanese and foreign scholars.
Frontmatter -- CONTENTS -- ACKNOWLEDGMENTS -- CONVENTIONS -- chapter 1. OPENING ORIENTATIONS -- chapter 2. FREEDOM OF EXPRESSION The Very Modern Practice of Visiting a Shinto Shrine -- chapter 3. TOWARD AN IDEOLOGY OF SACRED PL ACE -- chapter 4. KAMO MEMORIES AND HISTORIES -- chapter 5 WARDEN VIRTUOSO SALARYMAN PRIEST The Roles of Religious Specialists in Institutional Perspective -- chapter 6. PERFORMING RITUAL -- chapter 7. KAMIGAMO'S YEARLY RITUAL CYCLE -- CONCLUSION -- appendix 1. SYMBOLS, PAVILIONS, AND SIGNS AT KAMIGAMO SHRINE -- appendix 2 .KAMO-AFFILIAT E D S H R I N E S I N JAPAN -- NOTES -- select character glossary -- WORKS CITED -- INDEX.
Includes bibliographical references (pages 195-317) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
In English.
Keywords: Shinto; Shinto shrines; Shintō.; Sanctuaires shintō.; BODY, MIND & SPIRIT -- Spirituality -- Paganism & Neo-Paganism.; RELIGION -- Comparative Religion; RELIGION -- General; Shinto; Shinto shrines; Shintō; Sjintoïsme.; Shintō -- Japon; Temples shintō -- Japon; Japon -- Religion; Shinto; Shrines; Religion; History